2018 IEEE Radar Conference (RadarConf18) 2018
DOI: 10.1109/radar.2018.8378785
|View full text |Cite
|
Sign up to set email alerts
|

Beamforming P-band synthetic aperture radar for planetary applications

Abstract: The Space Exploration Synthetic Aperture Radar (SESAR) is an advanced P-band beamforming radar instrument concept to enable a new class of observations suitable to meet multiple Decadal Survey science goals for planetary exploration. The radar is capable of providing unprecedented surface and nearsubsurface measurements at full polarimetry and fine (meter scale) resolution, and achieves beam agility through programmable waveform generation and digital beamforming. The radar's highly flexible modular architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[ 14 ]. The concept of an aperture radar for space exploration with low mass and power consumption was introduced in [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ]. The concept of an aperture radar for space exploration with low mass and power consumption was introduced in [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted By NASA GSFC, Instrument Design Lab (IDL) (May 2013) concluded that the development of a compact, lightweight and power efficient radar transceiver module was a critical and necessary step in the implementation of this type of spaceborne SAR instrument For this reason, we have developed a prototype miniature Pband radar transceiver, directly applicable to two concepts for future spaceborne missions: The Carbon and Ecosystem Structure Agile SAR (CEASAR), and Space Exploration SAR (SESAR). [3]…”
Section: Introductionmentioning
confidence: 99%